Implementation of fiberglass in carbon fiber composites as an isolation layer that enhances lightning strike protection. (12th April 2019) - Guo, Yunli; Xu, Yongzheng; Zhang, Leian; Wei, Xiuting; Dong, Qi; Yi, Xiaosu; Jia, Yuxi
Abstract: In order to investigate the influence of anticorrosion-used fiberglass isolation layer on the lightning strike protection (LSP) of carbon fiber reinforced plastic (CFRP), the specimens, prepared by inserting a fiberglass layer between the expanded metal (Al or Cu) foil and CFRP substrate, were subjected to the artificial lightning of standardized Waveform C (200 Coulombs) and Waveform D (100 kA). The post-lightning damage was evaluated via visual inspection, ultrasonic scanning and residual strength test. The experiments found that the fiberglass isolation layer enhanced the LSP effectiveness of CFRP. While the majority of LSP solutions are based on the current "discharge" mechanism of highly conductive materials, the fiberglass isolation layer probably belongs to the "isolating" mechanism. The inherent electrically insulating, thermally insulating and refractory properties of fiberglass make it possible to construct an isolation layer that suppresses the downward penetration of lightning electric and heat into the underlying CFRP, preventing the CFRP from being ablated by internal Joule heat and external heat.